Analisis Pemungutan Pajak Parkir sebagai Pajak Barang dan Jasa Tertentu (PBJT) di Kota Bandar Lampung - Firmansyah Gemilang (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Parking tax collection as part of Specific Goods and Services Tax (PBJT) is an important source for increasing Local Own-Source Revenue (PAD). This policy is based on Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments and is implemented through Regional Regulation of Bandar Lampung City Number 1 of 2024. This study aims to examine the implementation of parking tax collection as PBJT as well as the supporting and inhibiting factors in its execution. The research employs normative juridical and empirical juridical approaches with a descriptive qualitative method. Data were collected through documentation studies and interviews with the Regional Revenue Management Agency (BPPRD) of Bandar Lampung City as the implementing institution. The results show that the implementation of PBJT on parking services in Bandar Lampung City uses a self-assessment system, where parking operators calculate, collect, report, and remit taxes independently through e-SPTPD and SIMANTAP managed by BPPRD. Supporting factors include clear regulations, the utilization of information technology, growth in the parking sector, and inter-agency support. Meanwhile, inhibiting factors include suboptimal taxpayer compliance, limited human resources within BPPRD, technical issues in the reporting system, and fluctuations in revenue due to seasonal factors. Overall, the implementation of PBJT on parking services has been effective but still requires improved supervision to optimize regional tax revenue.